A hydrothermal-carbonization process for simultaneously production of sugars, graphene quantum dots, and porous carbon from sugarcane bagasse. (June 2019) - Chai, Xinyu; He, Hui; Fan, Hanhan; Kang, Xiheng; Song, Xueping
Graphical abstract: Highlights: The best pretreatment conditions were 1:5, 170 °C, and 3 h for the HWP. FS, GQDs, and HPC were produced simultaneously by hydrothermal-carbonization process. The GQDs mainly derived from the dissolved lignin and polysaccharides in HWP process. The GQDs had small diameter and exhibited a spherical shape and graphene structure. The oxygen content and pore properties of HPC were controlled by HWP. Abstract: A green and facile approach was proposed to simultaneously produce fermentative sugar (FS), graphene quantum dots (GQDs), and hierarchical porous carbon (HPC) from sugarcane bagasse through the hydrothermal-carbonization process. In this work, the maximum yields of FS were 35.77%, 30.54%, 1.23%, 28.52%, and 41.85% for xylose, mannose, glucose, galactose, and arabinose, respectively. The GQDs, with bright blue fluorescence, had an average diameter at 2.26 nm, and exhibited a well-defined spherical shape and graphene structure. The formation mechanism of GQDs was further investigated, and the GQDs mainly derived from the dissolved lignin and polysaccharides. Moreover, the HPC presented a much higher surface area and controllable oxygen content than non-hydrothermal pretreatment porous carbon, whose unique pore structure was mainly resulted from the dissolution of FS. The green and facile approach provides a novel pathway to produce high value-added materials from sugarcane bagasse, developing a foundation for the preparation of better biomass materials.